THE EFFECTS OF SOME PREBIOTIC PRODUCTS (ACTIGEN, BIOTRONIC TOP3) ON THE PRODUCTION AND CONSUMPTION INDICES IN BROILER CHICKENS - Mihai Iacob Bentea (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2016)
The prebiotics are natural or synthetic organic substances that favour the growth of beneficial microorganisms in the gastro-intestinal tract, thus maintaining the animals healthy and productive and subsequently increasing the production performances. The aim of this study was to evaluate the effects of prebiotic products (Actigen and Biotronic Top3) on the main production and consumption indices of broilers. The study was conducted on a 75 broiler chicken Ross-308 hybrids divided in three groups, over a period of 42 days. Group 1(E) received combined feeds with the Actigen prebiotic for 42 days as follows: 0.08% in the starter phase (1-14 days), 0.04% in the grower phase (14-35 days) and 0.02% in the finisher phase (35-42 days). The broilers in group 2(E) were administered feeds containing prebiotic Biotronic Top3 (0.1%) for the whole duration of the study. The broilers in the control group were fed the base feed only. The broilers from all groups were weighed at the beginning and every following week; their average body weight, daily weight gain, feed consumption and feed conversion ratio (FCR) were determined. The use of the Actigen in experimental group 1(E) led to a body mass increase of 11.26%, to an 11.54% higher daily weight gain and to the reduction of the FCR by 2.31% compared to the control group. In Group 2(E) receiving Biotronic Top3, an increase was recorded for the body mass (9.25%) and daily weight gain (9.49%), the FCR being the same as the one recorded in the control group. These results confirm the favourable influence of prebiotics on the production performances of broiler chickens.